2021
DOI: 10.3389/fnagi.2021.691423
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Increase in Cholesterol Is Associated With Better Cognitive Function: Evidence From a Longitudinal Study

Abstract: Background: Higher visit-to-visit cholesterol has been associated with cognitive decline. However, the association between long-term increase or decrease in cholesterol and cognitive decline remains unclear.Methods: A total of 4,915 participants aged ≥45 years with normal cognition in baseline were included. The participants were divided into four groups, namely low–low, low–high, high–low, and high–high, according to the diagnostic thresholds of total cholesterol (TC), non-high-density lipoprotein cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Moreover, a randomized controlled trial suggests that triglyceride (TG) might be an alternative energy substrate for the brain and have positive effects on cognitive function (17). We also found a similar result that non-high-density lipoprotein cholesterol (NHDL-C) is associated with better cognition in middle-aged and elderly people (18). Collectively, the above findings suggest the complexity of the association between blood lipids and cognitive function.…”
Section: Introductionsupporting
confidence: 65%
“…Moreover, a randomized controlled trial suggests that triglyceride (TG) might be an alternative energy substrate for the brain and have positive effects on cognitive function (17). We also found a similar result that non-high-density lipoprotein cholesterol (NHDL-C) is associated with better cognition in middle-aged and elderly people (18). Collectively, the above findings suggest the complexity of the association between blood lipids and cognitive function.…”
Section: Introductionsupporting
confidence: 65%
“…The score of mental intactness was based on the number of correct answers, ranging from 0 to 11. According to previous studies (Zhou et al, 2020 ; Liu et al, 2021 ), we identified global cognition as the summation of episodic memory and mental intactness scores, and high scores reflect good cognitive function.…”
Section: Methodsmentioning
confidence: 99%
“…Those SNPs, related to a third variable such as cholesterol, may weaken the association between PRS for BMI and cognition. This is because we have found the protective role of cholesterol on cognition in our previous study ( Liu et al, 2021 ). On the other hand, however, PRS for BMI based on 97 GWS loci has been demonstrated to be associated with cardiometabolic traits, schizophrenia, irritable bowel syndrome, and Alzheimer’s disease, and overlaps with genes and pathways implicated in neurodevelopment, all of which were associated with cognitive impairment ( Locke et al, 2015 ).…”
Section: Discussionmentioning
confidence: 57%